DIGITAL TRANSFORMATION OF ECONOMIES THROUGH TECHNOLOGY, EDUCATION AND COMPETENCES - Uzule, Kristine; Gobniece, Zanda; Titko, Jelena (PROBLEMS OF EDUCATION IN THE 21ST CENTURY, 2024)
Digital transformation has profoundly impacted social and economic life by enhancing workforce competences, fostering innovation, and creating competitive advantages. Given that the driving force of digital transformation is technology, this study aimed to determine whether education and workforce competences are perceived as essential factors in the digital transformation narrative across diverse fields of socioeconomic development at both macro and micro levels. To achieve this, 528 abstracts from various scientific fields focused on digital transformation were analyzed using both manifest and latent content analyses, the latter ensuring a more objective interpretation of the outcomes derived from manifest content analysis. Frequency, word linkage, and concordance analyses of key concepts were used. The results indicated that education and workforce competences are viewed as vital for the digitalization of various sectors of the economy at both macro- and micro-level development. The findings suggest that technology drives digital transformation by delivering different types of value, including innovation and sustainability, while relying on education and technology-related competences. The results also revealed concerns about barriers to technology implementation, which could be overcome through education and competences. The originality of this research lies in its application of both manifest and latent analyses to identify the roles of education and technology in driving economic digital transformation.